ВПЛИВ ГІДРОХІМІЧНОГО РЕЖИМУ НА РОЗВИТОК ФІТОПЛАНКТОНУ В АКВАТОРІЇ НОВОРОСІЙСЬКОГО ПОРТУ (ЧОРНЕ МОРЕ) - Ясакова, О. Н.; Часовников, В. К. (Marine Ecological Journal, 2023)
The qualitative structure and quantitative development of the phytoplankton and hydro-chemical parameters of water in the port of Novorossiysk and open part of the bay during the spring – summer – autumn of 2007 have been studied. In total 70 species of the phytoplankton were found. Their species number (56) was found to be greater in summer; it is 25 % higher than in the spring and autumn. The maximal abundance and biomass of the phytoplankton (905.5 thousand cell/l; 2.767 g/m3) were fixed in May. These values in summer and autumn were 5 times lower, biomass - 2 times lower. The abundance of the phytoplankton in the western and central parts of the port was in 1.5 times higher than in open part of the bay. Biological index was correlated with hydro-chemical structure of the water and the highest concentration of nutrition elements was marked there.